Nepantla: Making a Space for Discomfort in an Elementary School Classroom - Emerson, Abby (Radical Teacher, 2018)
This teaching note demonstrates the way in which abstract concepts can be integrated into the elementary school classroom; specifically the work of Gloria Anzaldua into a 5th grade socio-emotional curriculum. The note calls for educators to make space for complexity and feelings of "in the middle" for their students.